Social talent scouting: A new opportunity for the identification of football players? - Radicchi, E.; Mozzachiodi, M. (Physical Culture and Sport. Studies and Research, 2016)
This paper investigates the diffusion of digital technologies within the football talent scouting process. A qualitative exploration based on open discussions and unstructured interviews with professionals involved in the football system (coaches, scouts, players` agents, etc.) provides insights about how new technologies are used for recruiting athletes. The findings, which are mainly in the context of Italian football, indicate a cultural and generational gap in the use of new digital tools that creates a mismatch between young promising athletes (demand side) and "senior" team professionals (supply side).